2020
DOI: 10.1002/iub.2420
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone ameliorates osteogenesis of human bone marrow mesenchymal stem cells against glucolipotoxicity through p38 MAPK signaling

Abstract: Diabetes mellitus (DM)-induced glucolipotoxicity is a factor strongly contributing to alveolar bone deficiency. Parathyroid hormone (PTH) has been identified as a main systemic mediator to balance physiological calcium in bone. This study aimed to uncover PTH's potential role in ameliorating the osteogenic capacity of human bone marrow mesenchymal stem cells (HBMSCs) against glucolipotoxicity. Optimal PTH concentrations and high glucose and palmitic acid (GP) were administered to cells, followed by alkaline ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Mechanistically, PTH activates both the p38 and c-Jun N-terminal kinases-mitogen-activated protein kinases (JNK-MAPK) signaling pathways by upregulating the phosphorylation of their respective subunits. It has been observed that a selective inhibitor targeting either p38 or JNK-MAPK signaling can weaken the effects of PTH on promoting increased osteogenic differentiation in SSCs [ 77 , 78 ]. However, in osteoarthritis (OA) patients, PTH (1-34) has been observed to inhibit the expression of type X collagen (COL10) and stimulate the expression of COL2 in SSCs.…”
Section: The Direct Interactions Of Pth With Bm Cellsmentioning
confidence: 99%
“…Mechanistically, PTH activates both the p38 and c-Jun N-terminal kinases-mitogen-activated protein kinases (JNK-MAPK) signaling pathways by upregulating the phosphorylation of their respective subunits. It has been observed that a selective inhibitor targeting either p38 or JNK-MAPK signaling can weaken the effects of PTH on promoting increased osteogenic differentiation in SSCs [ 77 , 78 ]. However, in osteoarthritis (OA) patients, PTH (1-34) has been observed to inhibit the expression of type X collagen (COL10) and stimulate the expression of COL2 in SSCs.…”
Section: The Direct Interactions Of Pth With Bm Cellsmentioning
confidence: 99%
“…The different glucose concentrations might account for the perplexing findings, which need further investigation. The dephosphorylation of p38 and suppressed p38-MAPK pathway have also been found to correlate with the impaired BMSCs osteogenesis under HG conditions ( 154 ). The potential regulatory of JNK in this process is less well understood.…”
Section: Impaired Bmscs Osteogenesis Under Hg Conditionsmentioning
confidence: 99%
“…PTH enhances the MSC survival rate by inhibiting their aging and apoptosis ( 81 ) and promotes MSC differentiation toward osteogenesis rather than adipogenesis ( 82 ). In the fight against glucolipotoxicity, PTH can promote osteogenic differentiation of BMSCs by activating the p38 MAPK signaling pathway ( 83 ). Moreover, in vivo studies have shown that human parathyroid hormone ( 1 34 ) has a positive effect on bone fracture healing in T2DM ( 84 ).…”
Section: Biochemical Cuesmentioning
confidence: 99%